2021
DOI: 10.1002/fsn3.2503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen regulation on berry quality and flavonoids during veraison stage

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…This may be because of the effects of ammonium sulfate in soil pH, nitrogen form (NH 4 + ), and/or sulfur present in the fertilizer. In different crops, an increase in TPC due to NH 4 + addition was reported [ 39 , 40 , 41 , 42 , 43 ]. In mustard, sulfur increased TPC [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be because of the effects of ammonium sulfate in soil pH, nitrogen form (NH 4 + ), and/or sulfur present in the fertilizer. In different crops, an increase in TPC due to NH 4 + addition was reported [ 39 , 40 , 41 , 42 , 43 ]. In mustard, sulfur increased TPC [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…This gene has been claimed to be a master regulator of nitrogen uptake by controlling more than half of the genes associated with nitrogen uptake and assimilation [107]. By considering that nitrogen regulation can effectively promote the improvement of berry components and the formation of flavor compounds in wine grapes [108], the fact that DYE treatment can modulate the expression of CRF4 is a topic that should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Britz E. et al [12] found that the crude protein content, mineral nutrient absorption, and crop yield of meadowsweet were significantly enhanced by increasing the nitrogen treatment. Hui Y et al [13] found that nitrogen application increased the levels of anthocyanins, flavanols, and flavonols in plants.…”
Section: Introductionmentioning
confidence: 99%